Collaborative watershed assessment: a profile of the Upper South Platte Partnership - Huayhuaca, Ch'aska, author; Colorado Forest Restoration Institute, publisher (Colorado State University. Libraries, 2016)
Water supplies critical to a variety of users originate in forested watersheds. These forests are prone to increasingly large and severe wildfires that can result in costly damage to water supplies and delivery systems. Reducing these risks has become a high priority for water providers in Colorado and across the interior West. The Upper South Platte Partnership (USPP) in Colorado is an instructive example of how to prioritize and coordinate wildfire mitigation actions at a watershed scale across jurisdictions.
Prepared for the Colorado Forest Restoration Institute.
Keywords: Water-supply -- Effect of fires on; Water-supply -- Colorado; Water-supply -- West (U.S.); South Platte River Watershed (Colo. and Neb.); Upper South Platte Partnership (USPP)